Corps en acte, entre virtuel et actuel - HORVÁTH, Eszter (Studia Universitatis Babeș-Bolyai Dramatica, 2015)
The Acting Body between Virtual and Actuality. Corporeality is one of the central problems of Jean-Luc Nancy’s philosophy. He invented the term “aréal”, which involves “area” and “non-real” at the same time, something not yet real, that already exists somewhere, something to become, something that will surge – the term implies creation, spacing, becoming, the process of realizing something to come. Thus, this term leads him to take into account the theatrical aspects of corporeality. Antonin Artaud is one of his favorite references in terms of theatrical corporeality. This paper tries to show the virtual cooperation between Nancy and Artaud in discovering the theatrical aspects of “being and becoming a body”.